Skin and bone: osteoma cutis as a diagnostic sign of Albright hereditary osteodystrophy. - Hernandez, L.; Vincent, N.; Romanelli, P.; Bellodi Schmidt , F. (European Journal of Pediatric Dermatology, 2023)
Osteoma cutis describes the process of bone formation within the skin. It is an uncommon but precise diagnosis when made histologically. While most cases of osteoma cutis are secondary to local processes such as acne, physicians must consider primary causes of osteoma cutis when encountering this finding in a child. In this report, we present an infant with osteoma cutis that led to the diagnosis of Albright hereditary osteodystrophy.